Controlador difuso basado en la tabla de búsqueda para controlar el proceso de la sala de vapor - Aminifar, Sadegh; Mohamad Kekshar, Sirwan; Daneshwar, Muhammadamin (Innovaciencia, 2018)
Introduction: In this paper, using look-up table control strategy,a fuzzy logic controller is designed for controlling the temperatureof steaming room in terrazzo tile plant corresponding to dedicatedprocess diagrams. Methods: In the proposed method, the temperature and error of temperature are considered as inputs to controlthe duration of valve open time to decrease the activation times ofvalves in order to increase their longevity. The strategy considersan off-line trained look-up table for setting the time of openingvalve in the specific temperature. A fuzzy controller with fifteen extracted rules is designed for controlling the duration of valve opentime. Results: Results show that the number of switching of valvereduces compare to intuitionistic or expert rule extraction. Conclusions: Simulations provide more compatible steaming process routcompare to PID controllers.